ENHANCING THE SENSORIMOTOR ABILITIES OF CHILDREN WITH SPECIAL NEEDS THROUGH MONTESSORI-BASED SENSORY TEXTURE BOARDS - Luluk Sugiarsih; Hamid Patilima; Rivo Panji Yudha (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to test the effectiveness of Montessori-based sensory texture boards in improving the sensory-motor abilities of children with special needs at Al Wardah Kindergarten, Peterongan District, Jombang Regency. The study used a quasi-experimental design with a one-group pretest-posttest design involving 40 children with special needs aged 4-6 years who were selected through a purposive sampling technique. The intervention was carried out for 8 weeks with a frequency of 2-3 times per week, a total of 10 sessions, using sensory texture boards designed based on Montessori principles. The research instrument was a sensory-motor ability observation sheet that had been validated by experts with high reliability. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed a very significant increase in children's sensory-motor abilities (Z = -5.238; p-value = 0.000). The average increase in ability was 29.15%, with 95% of subjects experiencing improvement. The highest improvement occurred in sensory perception (30.7%), followed by fine motor skills (30.6%), gross motor skills (29.6%), and sensory-motor integration (25.8%). This study concluded that Montessori-based sensory texture boards are effective as a learning medium for improving sensory-motor skills in children with special needs. The Montessori approach, which emphasizes independent exploration and learning through direct sensory experiences, has been shown to be well-suited to the needs of children with special needs.